Mappe di pericolosità e rischio idraulico nell'alluvione in Sicilia del 2018 (GEOmedia, 2021)
Floods, as a major natural disaster, affect many parts of the world, not including developed countries. Due to this natural disaster, every year there arelosses of human life and damage to the territory for millions of euros. Damage and losses can be prevented and limited by providing reliable informationto institutions and citizens through flood hazard models and maps (Demir, 2015). Hydraulic models and digital cartography are essential for municipalplanning, for civil protection emergency plans, for a correct design of works to prevent hydrogeological phenomena (Goodell and Warren, 2006). In thefirst days of November 2018, Sicily was affected by a phase of disturbed weather, characterized by intense and abundant rains that caused serious damageto the community and the territory.Geographical information systems (GIS) using spatial data are able to integrate hydraulic models for the simulation of flood events and are capable ofdrawing up maps of hydraulic hazard and estimating damage from hydrogeological instability (Demir, 2015). The GIS integrated with the hydraulicmodel is able to estimate the flood profile with a fixed return time. The hydraulic model used was developed after 1970 by the River Software AnalysisSystem (HEC-RAS) hydrological engineering center of the United States Army Corps of Engineers (USACE), and is now widely used in Europe andAmerica. GIS and HEC-RAS models have been successfully used to obtain flood maps of the Waller River in Texas (Tate et al., 2002), Ohio Swan RiverBasin (Wiles and Levine, 2002), Atrato River in Colombia (Mosquera-Machado and Ahmad, 2007), Vistula River in Warsaw, Poland (Gutry-Koryckaet al., 2006), the Gordon River in France (Sheffer et al., 2008), northwestern Colombia (Mosquera-Machado and Ahmad, 2007), central-eastern Dhakain Bangladesh (Masood and Takeuchi, 2012), and Onaville in Haiti (Heimhuber, 2015). Celik et al. analyzed the Kozdere Stream 2004 flood in Istanbulusing HEC-RAS and GIS (Celik et al., 2012). Sole et al. they have drawn up risk maps of the Basilicata region (Italy), generating profiles of free-flowingcurrents for different return times (30, 200 and 500 years) (Sole et al., 2007). Masood and Takeuchi used HEC-RAS and GIS to assess flood danger, vulnerabilityand hydraulic risk in Middle East Dhaka (Masood and Takeuchi, 2012), obtaining flood maps for floods with a 100-year return time. Sarhadiet al. investigated forecasting models of flooding in rivers in southeastern Iran using HEC-RAS and GIS (Sarhadi et al., 2012). Heimhuber et al. they usedHEC-RAS and GIS to perform the simulations in one-dimensional and non-stationary motion conditions for the design of the large Lan Couline channel(Heimhuber et al., 2015). The aim of this study is to study models to simulate scenarios for flood events in the Milicia River basin using the GIS andHEC-RAS for different return periods (50, 100 and 300).